Integrated Security for Smart Homes in IoT-Enabled Cities: Trust,Privacy, and Resilience – A Survey - Muhammad Furqan Zia; Maria Siddiqua (International Journal of Multidisciplinary Conference Proceedings (IJMCP), 2025)
The rapid growth of urban areas and advancements in information technology have paved the way for the development of smart cities and homes, leveraging the Internet of Things (IoT). Smart cities and homes represent the future of urban living, offering enhanced efficiency, convenience, and sustainability. This survey paper provides a comprehensive overview of the progress made in the domain of smart homes, focusing on the integration of IoT technologies. It explores the architectures, applications, devices, and communication technologies that have been implemented to achieve desired outcomes in smart home environments. Additionally, the paper highlights the key challenges researchers are addressing, particularly in the realm of security, to ensure the safe and reliable operation of smart homes within smart cities. By examining the current state of the art, this paper aims to provide insights into the future direction of secure smart homes and their role in the broader ecosystem of smart cities